Protein arginine methyltransferase 6 enhances ligand-dependent and -independent activity of estrogen receptor α via distinct mechanisms - Sun, Yang (2015)
Recent studies reported that protein arginine methyltransferase 6 (PRMT6) enhances estrogen-induced activity of estrogen receptor α (ERα) and dysfunction of PRMT6 is associated with overall better survival for ERα-positive breast cancer patients. However, it is unclear how PRMT6 promotes ERα activity. Here we report that PRMT6 specifically interacts with ERα at its ligand-binding domain. PRMT6 also methylates ERα both in vitro and in vivo. In addition to enhancing estrogen-induced ERα activity, PRMT6 over-expression up-regulates estrogen-independent activity of ERα and PRMT6 gene silencing in MCF7 cells inhibits ligand-independent ERα activation. More interestingly, the effect of PRMT6 on the ligand-independent ERα activity does not require its methyltransferase activity. Instead, PRMT6 competes with Hsp90 for ERα binding: PRMT6 and Hsp90 bindings to ERα are mutually exclusive and PRMT6 over-expression reduces ERα interaction with Hsp90. In conclusion, PRMT6 requires its methyltransferase activity to enhance ERα's ligand-induced activity, but its effect on ligand-independent activity is likely mediated through competing with Hsp90 for binding to the C-terminal domain of ERα. PRMT6-ERα interaction would prevent ERα-Hsp90 association. Since Hsp90 and associated chaperones serve to maintain ERα conformation for ligand-binding yet functionally inactive, inhibition of ERα-Hsp90 interaction would relieve ERα from the constraint of chaperone complex.